Employee Performance Based on Leadership and Work Motivation At PT. Astra Credit Companies TB Simatupang - Sunarto, Ading; Loloan, Rachel Ryana; Tanjung, Asridah Warni (Universitas Negeri Makassar, 2022)
This study aims to determine the influence of leadership and employee motivation on employee performance at PT. Astra Credit Companies TB Simatupang either partially or simultaneously. The method in this study is a quantitative method. Data analysis in this study uses validity test, reliability test, correlation coefficient analysis, classical assumption test, linear regression test, coefficient of determination analysis and hypothesis testing. The results showed that leadership (X1) had an effect on work performance (Y), with a simple linear regression equation Y = 15,743 + 0,528X and a significance value of 0.00 < 0.05. The correlation coefficient value is 0.605, which means that leadership (X1) has a strong level of relationship strength to employee performance (Y), with a coefficient of determination of 36.6% and from the t-test the value of tcount> ttable or 7.089 > 1988. Work motivation (X2) has an effect on work performance (Y) with a simple linear regression equation Y = 18,064 + 0.470X and a significance value of 0.00 <0.05. The correlation coefficient value is 0.512, which means that the work motivation variable (X2) has a moderate level of relationship strength on employee performance (Y), with a coefficient of determination of 26.2% and from the t-test, the value of tcount > ttable or 5,552 > 1,988. Leadership and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 15.638 + 0.515X1 + 0.017X2. The correlation coefficient value is 0.605, which means that leadership (X1) and work motivation (X2) simultaneously have a strong level of relationship strength on employee performance (Y), with a coefficient of determination of 36.6% and from the f test, the value of Fcount > Ftable or 24,849 > 3,100. This means that there is a simultaneous significant influence between leadership and work motivation on employees on employee performance at PT. Astra Credit Companies TB Simatupang.